Perancangan dan Implementasi Alat Penghitung Roti Otomatis Menggunakan Arduino Uno dan Modul Sensor Infrared - Muhammad Afifuddin Javan; Sumarno Sumarno; Jalaluddin Jalaluddin; Dedy Hartama; Ika Okta Kirana (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
This paper discusses the calculation of the amount automatically by using the principle of work of goods through the infahred sensor with reflecting light that mixes the light discovery items. This tool can work automatically because it is controlled by the ATmega328 microcontroller. The whole system consists of several components 1. Infrared sensors, 2. 16x2 LCDs, several jamper cables, bredbord, power supplies and several other devices. This step is to try the bread counter automatically. The test results of the design of the tool can work well in the process of selecting and calculating the amount of bread. Which will be sold to consumers.